2014
DOI: 10.1051/0004-6361/201423655
|View full text |Cite
|
Sign up to set email alerts
|

Shear mixing in stellar radiative zones

Abstract: Context. Turbulent transport of chemical elements in radiative zones of stars is considered in current stellar evolution codes thanks to phenomenologically derived diffusion coefficients. Recent local numerical simulations suggest that the coefficient for radial turbulent diffusion due to radial differential rotation satisfies D t 0.058κ/Ri, in qualitative agreement with the model of Zahn (1992, A&A, 265, 115). However, this model does not apply (i) when differential rotation is strong with respect to stable … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 43 publications
1
24
1
Order By: Relevance
“…In the small-Péclet-number regime, we showed (Prat & Lignières 2013) (Prat & Lignières 2014) as the Péclet number decreases, that is sensibly the same as in the SPNA. We can thus write…”
Section: Effect Of Thermal Diffusionsupporting
confidence: 73%
See 2 more Smart Citations
“…In the small-Péclet-number regime, we showed (Prat & Lignières 2013) (Prat & Lignières 2014) as the Péclet number decreases, that is sensibly the same as in the SPNA. We can thus write…”
Section: Effect Of Thermal Diffusionsupporting
confidence: 73%
“…In the large-Péclet-number regime (see Prat & Lignières 2014), the generalisation of Zahn's model proposed by Maeder (1995), intended to be also valid in this regime, turned to be incompatible with our simulations. In the opposite, we found a good agreement with the model of Lindborg & Brethouwer (2008), proposed in the geophysical literature, in which the diffusion coefficient is given by…”
Section: Effect Of Thermal Diffusioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The choice of the prescriptions for ν v and ν h can strongly affect the models outcomes [44] but is poorly constrained by observations. It can only be tested by numerical simulations, a work that [45] have undertaken with promising results.…”
Section: Hydrodynamical Instabilitiesmentioning
confidence: 99%
“…Prat & Lignières [129] discuss turbulent mixing in stellar radiative zones, pointing out that turbulent motions involved in rotating stars are full 3D motions, and cannot be easily resolved in models having fewer dimensions. Kitiashvili et al [130] use numerical radiation transfer simulations in 3D to study convective and oscillation properties of MS stars observed by Kepler and having masses of 1M and above; they find supersonic granular-type convection significantly larger than solar granulation, with strong overshooting plumes penetrating the stable radiative zone, potentially affecting oscillation properties.…”
Section: Stellar Evolution In Three Dimensionsmentioning
confidence: 99%